Principal Managerial in Creating Child Friendly Schools - Gusnimar Gusnimar; Qyoki Berty (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
This study aims to analyze and understand the managerial principles in creating child-friendly schools in the Pembina State Kindergarten, Padang Panjang City, West Sumatra. In this study, a phenomenological qualitative approach was used. The results of this study indicate that the implementation of child-friendly schools in the Pembina State Kindergarten of Padang Panjang City is carried out through various stages, namely SWOT Analysis, Branding Schools, Implementation of SRA Development, and Continuous Improvement. With the implementation of child-friendly schools in the Pembina State Kindergarten of Padang Panjang City, learning is more conducive and the trust of parents towards teachers is higher